Bridging Urban Housing Deficit in Ghana: An Assessment of the Challenges and Prospects of Private Sector Participation in Accra - Gyamfi, C. (University of Ghana, 2018)
Housing deficit is one of the major problems of urban managers. This has adversely led to the unbearable demand for public infrastructure such as social housing; roads; sewage works; water and sanitation; ports; electrification; health care; telecommunication networks; education and security; entertainment transportation; public health institutions; and employments poverty, pollution, overcrowding, congestion and shortage of affordable housing in the urban centers. This study focused on the challenges and prospects of the private sector in trying to bridge the urban housing deficit in the Accra metropolis. The objective was to identify the housing deficit trends, identify the incentive package as well as the challenges that the private sector goes through in their quest to reducing the housing deficit in the urban areas of Ghana, specifically, Accra. A sample of 66 respondents were selected from 11 real estate companies from the Accra metropolis. The study found out that over the 11 years period, there was a steady increase in the number of housing units built by the private sector, though not enough to meet the urban population growth, however declined drastically in 2015.The study contends that there are some major causes of housing deficits in the country and was attributed to influx of people into the capital in search for a greener pastures. The study also revealed that the abolishment of major taxes on their operations by the new government serve as a major boost in their activities. Also, the study revealed that even though a lot has been done in terms of the reforms in the industry, majority of the respondents believe that government can do a lot more, especially with the eradication of middlemen in land acquiisition that often leads to land litigations. The study recommends that urban housing deficit can be solved or the trend can be reversed if through collaborative governance, good public-private partnership, and minimal or no political interference. Also, government incentives should be visible and not mere rhetorics as well listing on the stock exchange for investment and ownership.
MPA.
Keywords: Urban Housing; Ghana; Private Sector; Accra